2017
DOI: 10.1186/s12881-017-0438-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between male infertility and ancestry in South Americans: a case control study

Abstract: BackgroundInfertility affects 15% of human couples, with men being responsible in approximately 50% of cases. Moreover, the aetiology of male factor infertility is poorly understood. The majority of male factor infertility remains idiopathic and potentially genetic in origin. The association of the Y chromosome and mitochondrial haplogroups with male infertility has been previously reported. This association differs between studied populations and their geographical distributions. These effects have been only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…Asthenospermia was identified by reduction in sperm motility lower than 40% motile sperms. Accordingly, Skowronek et al (2017) identified oligozoospermia with less than 15 million sperms per ml semen. These authors classified asthenozoospermia by total sperm motility less than 32%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asthenospermia was identified by reduction in sperm motility lower than 40% motile sperms. Accordingly, Skowronek et al (2017) identified oligozoospermia with less than 15 million sperms per ml semen. These authors classified asthenozoospermia by total sperm motility less than 32%.…”
Section: Discussionmentioning
confidence: 99%
“…One of the M subhaplogroup (M25) was found in infertile men of the present study. Inversely, Skowronek et al (2017) found that Americans with haplogroup F of the Y chromosome were highly frequent with teratospermia. The authors claimed that there was no correlation between sperm parameters and the haplogroups predicted from mitochondrial DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R1a and E in a study of 338 azoospermic/oligozoospermic patients from different ethnic backgrounds in the Balkans (Kuzmanovska et al, 2019), and also for haplogroup F(xK) with abnormal sperm morphology in Uruguayan (Skowronek et al, 2017), Q1a3a with AZFb deletions in Chilean (Lardone et al, 2013), and K* with azoospermia/ oligozoospermia in Latvian population (Puzuka et al, 2011).…”
Section: Zhang Et Al Typed Complete and Partial Azfc Deletions Alongmentioning
confidence: 99%
“…[ 1 , 2 ] Male factors account for ∼50% of infertile couples who are unable to conceive, due to marital and psychosocial stress. [ 3 ] Many factors have an adverse impact on male reproductive health, including lifestyle, [ 4 , 5 ] intratesticular varicocele, [ 6 ] varicocele, [ 7 9 ] ancestry, [ 10 ] SNPs, [ 11 , 12 ] etc. Unfortunately, the pathogenesis of this disease remains unknown.…”
Section: Introductionmentioning
confidence: 99%